Pelatihan Pengelolaan Bahasa Iklan Media Sosial dalam Pemasaran Produk Desa Lembuak, Kecamatan Narmada - Syafira Mahfuzi Ardiyati; Rahman Prasetyo; Stevany Hanalyna Dethan; Husain Husain; M. Najmu Fadli (Pusat Riset dan Inovasi Nasional, 2024)
The rapid development of technology is often used to promote products, especially small and medium enterprises or MSMEs. Social media is used to convey product information and help with marketing. However, often less attention is paid to the management of advertising language on social media. Clan language is needed to attract buyers' attention and convince buyers about the quality of the products offered by MSMEs. MSMEs in Lembuak District, Narmada were the choice for this training because many people are engaged in the MSME business. When promoting products, it was found that many people used monotonous sentences, so that income through online promotions was still lower than offline promotions.